Impact of vegetation restoration on soil moisture dynamics in temperate water-limited regions - Lihua Lan; Tingting Zhang; Fei He; Baolin Wang; Junwei Bao (Journal of Hydrology: Regional Studies)
Study region: Temperate water-limited regions in northern China. Study focus: While restoring vegetation in China’s temperate water-limited regions is crucial for combating desertification, its hydrological effects—whether causing soil moisture (SM) drying or wetting—remain a topic of debate. This study quantified their time-dependent interactions to evaluate phase-dependent SM responses, clearly separating the contributions of vegetation-mediated effects, climatic influences, and vegetation-climate interactions. New hydrological insights for the region: The results revealed contrasting trends between vegetation and SM across two phases. In T1 (1981–1999), NDVI significantly increased (0.0025/yr, p = 0.05) over 73 % of the area, with SM also rising (0.001 m³/m³/yr, p = 0.5) in 61 %. In T2 (2000–2020), NDVI growth accelerated (0.006/yr, p = 0.03) in 75 % of the area, while SM declined (-0.0007 m³/m³/yr, p = 1.0) in 59 %. Partial least squares structural equation modeling (PLS-SEM) identified distinct spatiotemporal drivers of SM dynamics. During T1, meteorological-vegetation interactions dominated SM increases across 60.3 % of the study area. In contrast, during T2, NDVI became the primary driver (60.7 % coverage), correlating with widespread SM declines. This quantitative framework delineated competing controls on SM and supported adaptive vegetation management in water-limited ecosystems.